Selective inhibition of polymorphonuclear neutrophils by resuscitative concentration of hypertonic saline - Choi, S H (BMJ Group, 2006)
OBJECTIVES: This study investigated the effect of hypertonic saline on the role of polymorphonuclear neutrophils (PMNs) in the inflammatory response and the effect of hypertonic saline infused at different phases in relation to an inflammatory stimulus. MATERIALS AND METHODS: PMNs were isolated from peripheral blood of healthy volunteers (Boyum's method) and cultured in three different media ([Na(+)] = 140 mmol/l, 180 mmol/l, and 200 mmol/l). PMNs were then stimulated with fMLP (N‐formyl‐methionyl‐leucyl‐phenylalanine) and H(2)O(2) synthesis was quantified by flow cytometry at 5, 30, 60, 120, and 180 minutes. PMNs were treated with hypertonic saline before, simultaneously with, and after fMLP stimulation, and H(2)O(2) synthesis quantified again. RESULTS: H(2)O(2) synthesis was two or three times higher in fMLP stimulated than in non‐stimulated PMNs, and it reached maximum level at 120 minutes. In the absence of fMLP stimulation, there was no significant difference between control and hypertonic saline with regard to activity of H(2)O(2) synthesis. In the presence of fMLP stimulation, H(2)O(2) synthesis significantly decreased in PMNs treated with hypertonic saline. There was no significant difference between the two hypertonic saline solutions ([Na(+)] = 180 mmol/l and 200 mmol/l) with regard to H(2)O(2) synthesis. However, H(2)O(2) synthesis decreased in PMNs treated with hypertonic saline before and simultaneously with fMLP stimulation, but was not significantly decreased in the cells treated with hypertonic saline after fMLP stimulation. CONCLUSIONS: Hypertonic saline appears to decrease H(2)O(2) in stimulated neutrophils. This may be a further beneficial role of hypertonic saline when used clinically as an early resuscitation fluid.